2015
DOI: 10.1016/j.stem.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9-Mediated Genetic Screening in Mice with Haploid Embryonic Stem Cells Carrying a Guide RNA Library

Abstract: In the version of our paper originally published online on July 9, 2015, under the Experimental Procedures subsection ''Derivation of AG-haESCs,'' we included the line, ''Each embryo was transferred into one well of a 96-well plate seeded with ICR embryonic fibroblast feeders in ESC medium supplemented with 20% knockout serum replacement, 1,500 U/ml LIF, 3 M CHIR99021, and 1 M PD0325901.'' However, the concentrations of CHIR99021 and PD0325901 should have been written as 3 mM CHIR99021 and 1 mM PD0325901, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…We first examined the feasibility of semi-cloning technology to generate mouse models of DM1 carrying a single mutant gene by injection of haploid cells carrying a mutation in Dmpk, Six5 or Mbnl1, the three well-studied DM1-related genes. A haploid cell line (termed H19 ΔDMR -IG ΔDMR -AGH or O48) that has been reported to efficiently support SC mouse generation 43 was used in this study. We generated haploid ESC lines carrying mutant Dmpk, Six5 or Mbnl1 (referred to as ΔDmpk-O48, ΔSix5-O48 and ΔMbnl1-O48, respectively) (Supplementary information, Figs.…”
Section: Generation Of a Novel Dm1 Model Carrying Mutations In Dmpk mentioning
confidence: 99%
See 1 more Smart Citation
“…We first examined the feasibility of semi-cloning technology to generate mouse models of DM1 carrying a single mutant gene by injection of haploid cells carrying a mutation in Dmpk, Six5 or Mbnl1, the three well-studied DM1-related genes. A haploid cell line (termed H19 ΔDMR -IG ΔDMR -AGH or O48) that has been reported to efficiently support SC mouse generation 43 was used in this study. We generated haploid ESC lines carrying mutant Dmpk, Six5 or Mbnl1 (referred to as ΔDmpk-O48, ΔSix5-O48 and ΔMbnl1-O48, respectively) (Supplementary information, Figs.…”
Section: Generation Of a Novel Dm1 Model Carrying Mutations In Dmpk mentioning
confidence: 99%
“…Recently, mouse androgenetic haploid embryonic stem cells (AG-haESCs) have been successfully developed as sperm replacement to efficiently produce semi-cloned (SC) animals by injection into oocytes (intracytoplasmic AG-haESC injection, ICAHCI). [43][44][45] AG-haESCs enable efficient and stable onestep generation of mice with multiple heterozygous mutant genes by ICAHCI of haploid cells carrying these mutations, 43 allowing production of sufficient numbers of SC offspring for analyses in one generation. Thus, the haploid ESC-mediated semi-cloning technology may provide an ideal tool to generate mouse models with multiple heterozygous mutant genes in one step to mimic the reduced expression of multiple genes in human complex diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it was reported that with H19-and IG-DMRs being knocked out, ahESCs can stably retain the developmental potential and exhibit comparable "fertilizing" capacity as round spermatids (Fig. 4) (Zhong et al, 2015).…”
Section: Replacing the Gametes By Haescsmentioning
confidence: 99%
“…The generation of CRISPR/Cas9 knock-in mice (84) facilitates such screening because primary cells generated from Cas9 transgenic mice will have Cas9 stably integrated in the genome. Efforts have been made to develop convenient methods for generating CRISPR sgRNA library-based knockout mice for genetic screening (137). For example, a pooled CRISPR screening has taken advantage of this approach by generating bone marrow-derived dendritic cells from Cas9 mice and screening for regulatory factors of innate immune circuits responsible for the host response to pathogens (80).…”
Section: Crispr/cas9 Nuclease Function-based Loss-of-function Screeningmentioning
confidence: 99%